On the Origins of Dishonesty: From Parents to Children - Daniel Houser; John A. List; Marco Piovesan; Anya Samek; Joachim K. Winter (Institute for the Study of Labor (IZA), 2015)
Acts of dishonesty permeate life. Understanding their origins, and what mechanisms help to attenuate such acts is an underexplored area of research. This study takes an economics approach to explore the propensity of individuals to act dishonestly across different economic environments. We begin by developing a simple model that highlights the channels through which one can increase or decrease dishonest acts. We lend empirical insights into this model by using an experiment that includes both parents and their young children as subjects. We find that the highest level of dishonesty occurs in settings where the parent acts alone and the dishonest act benefits the child rather than the parent. In this spirit, there is also an interesting effect of children on parents' behavior: in the child's presence, parents act more honestly, but there are gender differences. Parents act more dishonestly in front of sons than daughters. This finding has the potential of shedding light on the origins of the widely documented gender differences in cheating behavior observed among adults.
Keywords: C91; D63; 330; cheating; dishonesty; ethical judgment; social utility; field experiment